2015
DOI: 10.3109/01480545.2014.975355
|View full text |Cite
|
Sign up to set email alerts
|

−NMDA R/+VDR pharmacological phenotype as a novel therapeutic target in relieving motor–cognitive impairments in Parkinsonism

Abstract: Our findings suggest that calcium mediated toxicity is primary to the cause and progression of Parkinsonism and targeting receptors that primarily modulates calcium reduces the morphological and behavioral deficits in drug induced Parkinsonism. VDR activation was more effective than NMDAR inhibition and a combined intervention. We conclude that targeting VDR is key for controlling calcium toxicity in drug/chemotoxin induced Parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Interestingly, normal neural activity was restored after VD 3 RA treatment in vivo. In addition, immunohistochemical demonstration of neuron and astrocyte populations revealed an increase in cell proliferation in the M1 post VD 3 RA treatment and corroborated the improved motor-cognitive function observed in behavioural studies [20]. The current study examines the role of prolonged haloperidol use in D 2 sensitivity in the motor-cognitive neural axis.…”
Section: Introductionsupporting
confidence: 74%
“…Interestingly, normal neural activity was restored after VD 3 RA treatment in vivo. In addition, immunohistochemical demonstration of neuron and astrocyte populations revealed an increase in cell proliferation in the M1 post VD 3 RA treatment and corroborated the improved motor-cognitive function observed in behavioural studies [20]. The current study examines the role of prolonged haloperidol use in D 2 sensitivity in the motor-cognitive neural axis.…”
Section: Introductionsupporting
confidence: 74%
“…Haloperidol has been involved in the interference in the trafficking of different glutamate receptors in vivo as NMDA associated with calcium-calmodulin dependent kinase in rat frontal cortex [7]. There has also been found a relationship among the block of dopaminergic D 2 receptors and some motor-cognitive impairment in animals with Parkinsonism due to interactions in targeting calcium controlling receptors as NMDA receptors and Vitamin D 3 receptors (VDR) in brain [8]. In fact, the specific activation of the VDR was more effective in protecting motor-cognitive function and neural activity than the inhibition of the NMDA receptor [8].…”
Section: Discussionmentioning
confidence: 99%
“…There has also been found a relationship among the block of dopaminergic D 2 receptors and some motor-cognitive impairment in animals with Parkinsonism due to interactions in targeting calcium controlling receptors as NMDA receptors and Vitamin D 3 receptors (VDR) in brain [8]. In fact, the specific activation of the VDR was more effective in protecting motor-cognitive function and neural activity than the inhibition of the NMDA receptor [8]. These results suggest that chronic treatment with haloperidol can induce a tardive dyskinesia due to hyperactivity of glutamate receptors in motor areas in the brain, especially involved in involuntary movements.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments have shown that activation of Vitamin D 3 receptor (VD 3 R) reduces calcium toxicity through central and peripheral mechanisms, and improves motor-cognitive function in mice after haloperidol induced parkinsonism [13]. In the present study, we investigate the link between haloperidol-induced dyskinesia and M1, CPu, PFC and CA1 neural activities in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Dyskinesia was induced using 10 mg/Kg BW of dopaminergic D 2 blocker (Haloperidol i.p. 28 days) in n = 12 animals [13] [14]. Subsequently, n = 6 animals were treated with 100 mg/Kg BW (i.p.…”
Section: Animal Treatmentmentioning
confidence: 99%